Nicotinamide nucleotide transhydrogenase: a link between insulin secretion, glucose metabolism and oxidative stress. - Freeman, H; Shimomura, K; Cox, R; Ashcroft, F (2006)
This paper reviews recent studies on the role of Nnt (nicotinamide nucleotide transhydrogenase) in insulin secretion and detoxification of ROS (reactive oxygen species). Glucose-stimulated insulin release from pancreatic beta-cells is mediated by increased metabolism. This elevates intracellular [ATP], thereby closing KATP channels (ATP-sensitive potassium channels) and producing membrane depolarization, activation of voltage-gated Ca2+ channels, Ca2+ influx and, consequently, insulin secretion. The C57BL/6J mouse displays glucose intolerance and reduced insulin secretion, which results from a naturally occurring deletion in the Nnt gene. Transgenic expression of the wild-type Nnt gene in C57BL/6J mice rescues the phenotype. Knockdown of Nnt in the insulin-secreting cell line MIN6 with small interfering RNA dramatically reduced Ca2+ influx and insulin secretion. Similarly, mice carrying ENU (N-ethyl-N-nitrosourea)-induced loss-of-function mutations in Nnt were glucose intolerant and secreted less insulin during a glucose tolerance test. Islets isolated from these mice showed impaired insulin secretion in response to glucose, but not to the KATP channel blocker tolbutamide. This is explained by the fact that glucose failed to elevate ATP in Nnt mutant islets. Nnt is a nuclear-encoded mitochondrial protein involved in detoxification of ROS. beta-Cells isolated from Nnt mutant mice showed increased ROS production on glucose stimulation. We hypothesize that Nnt mutations enhance glucose-dependent ROS production and thereby impair beta-cell mitochondrial metabolism, possibly via activation of uncoupling proteins. This reduces ATP production and lowers KATP channel activity. Consequently, glucose-dependent electrical activity and insulin secretion are impaired.